Spells for forgetting eaudiobook A novel. - Young, Adrienne (Random House Audio, 2022)
NATIONAL BESTSELLER • “Lush with secrets, magic, and a past that won’t stay where it belongs, this novel is (quite fittingly) spellbinding.”—JODI PICOULT, author of Wish You Were Here A deeply atmospheric story about ancestral magic, an unsolved murder, and a second chance at true love ONE OF THE BEST BOOKS OF THE YEAR: She Reads Emery Blackwood’s life changed forever the night her best friend was found dead and the love of her life, August Salt, was accused of murdering her. Years later, she is doing what her teenage self swore she never would: living a quiet existence on the misty, remote shores of Saoirse Island and running the family’s business, Blackwood’s Tea Shoppe Herbal Tonics & Tea Leaf Readings. But when the island, rooted in folklore and magic, begins to show signs of strange happenings, Emery knows that something is coming. The morning she wakes to find that every single tree on Saoirse has turned color in a single night, August returns for the first time in fourteen years and unearths the past that the town has tried desperately to forget. August knows he is not welcome on Saiorse, not after the night everything changed. As a fire raged on at the Salt family orchard, Lily Morgan was found dead in the dark woods, shaking the bedrock of their tight-knit community and branding August a murderer. When he returns to bury his mother’s ashes, he must confront the people who turned their backs on him and face the one wound from his past that has never healed—Emery. But the town has more than one reason to want August gone, and the emergence of deep betrayals and hidden promises spanning generations threaten to reveal the truth behind Lily’s mysterious death once and for all.